HRP-integrated CRISPR-Cas12a biosensor for rapid point-of-care detection of Langya henipavirus - Xuan Wu; Rong Xiang; Danting Yang; Xiaoyao He; Lu Zhu; Fangfang Sun; Hanqing Li; Ningning Pi; Yi Li (iScience)
Summary: Global pandemic has emphasized the needs for advanced pathogen diagnosis in dealing with newly emerged infectious threats, including the Langya henipavirus (LayV). LayV, as an emerging zoonotic pathogen, has potential to cause pandemic, but lacks of rapid diagnostic tools, particularly at point-of-care level. Here, we leveraged the merits of CRISPR-Cas12a biosensing and established a highly sensitive LayV detection method. By integrating CRISPR-Cas12a with RPA, 10 copies/μL ultra-sensitive LayV RNA detection has been achieved at room temperature within 30 min. More importantly, this study developed a special horseradish peroxidase (HRP)-single-stranded DNA (ssDNA) reporter enabling CRISPR-Cas12a to detect LayV RNA without pre-amplification, achieving a sensitivity of 1,200 copies/μL detectable by the naked eye. These explorations can serve as accelerator for CRISPR-Cas biosensing toward rapid response for newly emerged biological threats, and also provide a method to realize simple, precise, and amplicon-free point-of-care pathogen screening for resource limited or underdevelopment regions.